Pengaruh Struktur Modal, Profitabilitas dan Tax Avoidance terhadap Nilai Perusahaan: Studi Empiris Pada Perusahaan Sektor Kesehatan Yang Terdaftar Di Bursa Efek Indonesia Pada 2020-2024 - Effendy, Michaela Agnes Faustina; Khotimah, Husnul (Prisani Cendekia, 2025)
This study aims to analyze the influence of capital structure, profitability, and Tax Avoidance on the value of companies in the healthcare sector listed on the Indonesia Stock Exchange. A quantitative approach was used to assess the relationship between variables using secondary data from annual financial reports. The analysis was conducted using a panel data regression model to test the consistency of each variable's influence. The results indicate that profitability plays a significant role in increasing company value through the ability to generate stable and sustainable profits. Conversely, capital structure and Tax Avoidance do not significantly influence investor perceptions. These findings emphasize the importance of managing profitability as a positive signal to the market, while financing policies and tax strategies need to be carefully directed to avoid reducing investor confidence in the company's long-term performance.